2021
DOI: 10.3389/fimmu.2021.692216
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Intrinsic Myd88 Directs the Production of Antibodies With Specificity for Extracellular Matrix Components in Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome is an autoimmune disease that is predominantly seen in women. The disease is characterized by exocrine gland dysfunction in combination with serious systemic manifestations. At present, the causes of pSS are poorly understood. Pulmonary and renal inflammation are observed in pSS mice, reminiscent of a subset of pSS patients. A growing body of evidence indicates that inflammation mediated by Damage-Associated Molecular Patterns (DAMPs) contributes to autoimmunity, although this is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…5 Journal of Immunology Research and kidney tissues of pSS mice [79]. Our study also found that decorin was significantly elevated in the salivary glands in the experimental Sjögren's syndrome model and pSS patients, and decorin induced the apoptosis of A253 cells and polarization of macrophages towards the M1 phenotype [54].…”
Section: Sscsupporting
confidence: 70%
See 1 more Smart Citation
“…5 Journal of Immunology Research and kidney tissues of pSS mice [79]. Our study also found that decorin was significantly elevated in the salivary glands in the experimental Sjögren's syndrome model and pSS patients, and decorin induced the apoptosis of A253 cells and polarization of macrophages towards the M1 phenotype [54].…”
Section: Sscsupporting
confidence: 70%
“…This indicates that decorin may have a different effect on different cytokines/chemokines and immune cells in SS. Further studies showed that although circulating levels of decorin were not different between NOD.B10 mice and control mice, autoantibodies against decorin were significantly elevated in pSS mice, and decorin was highly expressed in the salivary gland, lung, and kidney tissues of pSS mice [ 79 ]. Our study also found that decorin was significantly elevated in the salivary glands in the experimental Sjögren's syndrome model and pSS patients, and decorin induced the apoptosis of A253 cells and polarization of macrophages towards the M1 phenotype [ 54 ].…”
Section: Decorin In Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
“…While there is no difference in the expression of Bgn and Dcn in the SGs of healthy and SS control mice, Kiripolsky et al demonstrated that SS mice displayed increased levels of anti-Bgn and -Dcn autoantibodies relative to healthy controls. 36 Thus, emerging evidence suggests that degradation of the SG-ECM and basal lamina may precede (or take place in parallel with) the onset of inflammation, which is widely considered the ultimate cause of SS development. These findings suggest that potential therapies, which aim to restore a healthy SG microenvironment, may be a very promising, if relatively unexplored, therapeutic avenue.…”
Section: Pathogenesis Of Two Major Types Of Sg Pathologiesmentioning
confidence: 99%
“…6). In the pathological state, ECM components can serve as damage-associated molecular patterns (DAMPs) that exacerbate and perpetuate inflammatory cascades and may provide a novel source of chronic B cell activation in SjS [63].…”
Section: Discussionmentioning
confidence: 99%